FACTORS THAT INFLUENCE COMPLAINTS OF RESPIRATORY DISORDERS ON PARKING OFFICERS IN URBAN, GORONTALO CITY - Irwan Irwan; Moh Rivai Nakoe; Nofyarahmat Musa (Gorontalo State University, 2022)
AbstrakSistem pernafasan memiliki peran sangat penting mempengaruhi aktivitas dan kehidupan. Penyakit saluran pernapasan pada umumnya dimulai dengan keluhan- keluhan dan gejala-gejala yang ringan. Tujuan penelitian ini untuk mengetahui faktor resiko yang mempengaruhi gangguan keluhan pernafasan pada petugas parkir, Kebaruan penelitian ini meneliti variabel perilaku merokok dan penggunaan Alat pelindung diri sebagai faktor resiko gangguan pernafasan. Metode penelitian yang digunakan yaitu metode kuantitatif dengan pendekatan Cross Sectional. Populasi dan sampel pada penelitian ini adalah seluruh petugas parkir di Perkotaan Kota Gorontalo yang tercatat berdasarkan data sekunder Dinas Perhubungan Kota Gorontalo yaitu 85 responden. Analisis data menggunakan uji statistik Chi- Square. Hasil penelitian untuk faktor umur dalam kategori ≥ 30 Tahun sebanyak 34 responden (85,0%), faktor perilaku merokok dalam kategori merokok sebanyak 32 responden (80,0%), faktor masa bekerja dalam kategori ≥ 3 Tahun sebanyak 30 responden (75,0%), faktor penggunaan APD dalam kategori tidak menggunakan sebanyak 34 responden (85,0%) dan faktor keluhan gangguan pernafasan dalam kategori ada gangguan sebanyak 36 responden (90,0%). Simpulan penelitian terdapat pengaruh faktor umur, perilaku merokok, masa bekerja dan penggunaan APD dengan keluhan gangguan pernafasan pada petugas parkir di Kota Gorontalo. Kata Kunci : Merokok; Masa bekerja; APD; Keluhan Pernafasan; Petugas Parkir. Abstract The respiratory system has a very important role in influencing activities and life. Respiratory tract disease generally begins with mild complaints and symptoms. The purpose of this study was to determine the risk factors that influence respiratory complaints in parking attendants. The novelty of this study examined the variables of smoking behavior and the use of personal protective equipment as risk factors for respiratory disorders.The research method used is a quantitative method with a Cross Sectional approach. The population and sample in this study were all parking attendants in Gorontalo City which were recorded based on secondary data from the Gorontalo City Transportation Service, namely 85 respondents. Data analysis used Chi-Square statistical test. The results of the study for the age factor in the category 30 years as many as 34 respondents (85.0%), smoking behavior factors in the smoking category as many as 32 respondents (80.0%), the working period factor in the category 3 years as many as 30 respondents (75, 0%), the factor of using PPE in the category of not using as many as 34 respondents (85.0%) and the factor of respiratory complaints in the category of having disturbances as many as 36 respondents (90.0%). The conclusion of the study is based on calculations using the Chi-Square statistical test that there is an influence between factors of age, smoking behavior, years of work and the use of PPE with complaints of respiratory problems.